The carbonate system and air-sea CO2 fluxes in coastal and open-ocean waters of the Macaronesia - Curbelo-Hernández, David; González-Dávila, Melchor; Santana-Casiano, J. Magdalena (Frontiers in Marine Science, 2023)
The CO2 system, anthropogenic carbon (Cant) inventory and air-sea CO2 fluxes (FCO2) were analysed in the archipelagic waters of the Macaronesian region. The (sub)surface data were collected during POS533 (February and March, 2019) in coastal areas leeward of Cape Verde (CV), Canary Islands (CA) and Madeira (MA) and through the vessel track. The CO2 variability was controlled by changes in temperature, biological activity and advection processes forced by spatial heterogeneities in the Canary Upwelling System, the mixed layer depth, the mesoscale activity and the circulation patterns. The surface fCO2,sw variability was driven by biological production and CO2-rich water injection in tropical waters and by temperature fluctuations in subtropical waters. The factors controlling the upper ocean changes in the total inorganic carbon normalized to a constant salinity (NCT) were assessed. The uptake and storage of anthropogenic carbon, calculated by using the TrOCA 2007 approach described, as an upper limit, > 60% (>90% above the MLD) of the NCT increase from preformed values. The organic carbon pump accounted 36.6-40.9% for tropical waters and lose importance for subtropical waters (7.5-11.6%), while the carbonate pump has a minimal contribution (<4.2%). The upper-ocean Cant inventory in coastal areas of CV (8,570 Km2), CA (7.960 Km2) and MA (1,250 Km2) was 7.57 x 103, 9.26 x 103 and 8.86 x 103 µmol kg-1, respectively (0.51, 0.58 and 0.09 Tg C, respectively). In terms of FCO2, the CV, CA and MA behaved as a winter CO2 sink (-4.74, -3.90 and -8.34 mmol m-2d-1, respectively) while a strong outgassing was detected over the Cape Blanc filament (20-25 mmol m-2d-1). The total average FCO2 for the ocean area of the three archipelagos (371,250 Km2) was -28.27 Gg CO2 d-1. The POS533 data were compared and compilated with SOCAT and GLODAP data and a new set of equations was provided to calculate the fCO2,sw, Cant and FCO2 in the Macaronesian region based on physical and biogeochemical properties.